New light on William Babell's development as a keyboard composer. (25th June 2018) - Woolley, Andrew
Abstract: This article gives a detailed description of Bergamo, Biblioteca Musicale Gaetano Donizetti, Ms. xiv 8751 h .1, proposing that it is an important collection of music by William Babell (1688–1723), an English composer of German birth. Additionally, it discusses Babell's borrowings from the French organist Jean-François Dandrieu (1681–1734), among them one of the movements from the harpsichord suite hwv 441. This suite was published at the end of John Walsh's unauthorized 'Second Volume' of Handel's harpsichord music (1733), but is included in the Bergamo manuscript. The article also sheds light on Babell's relationship with Handel's music.